Inflation, Human Capital and Tobin's q - Parantap Basu; Max Gillman; Joseph Pearlman (Hungarian Academy of Sciences, Institute of Economics, 2010)
A less well-known empirical finding for the US and UK is a pronounced low frequency negative relationship between inflation and Tobin's q; a normalized market price of capital. This stylized fact is explained within a dynamic stochastic general equilibrium model using three key features: (i) a Lucas and Prescott (1971) physical capital adjustment cost with a rising marginal cost of investment, (ii) production of human capital with endogenous growth and (iii) an inflation tax cash-in-advance economy. The baseline endogenous growth model matches the US inflation and q long term correlation, while comparable exogenous growth are unable to do this, and it outperforms the exogenous growth models in explaining business cycle volatilities of q and of stock returns.
Keywords: E31; E44; G12; 330; Low frequency; Tobin's q; inflation tax; endogenous growth; Inflation; Tobins Q; Endogenes Wachstumsmodell; Dynamisches Gleichgewicht; USA; Großbritannien